IMPLEMENTASI PEMBELAJARAN SAINS BERBASIS ALAM DI SMP SEKOLAH ALAM CIKEAS-BOGOR - Hakiki, Ari; Lathifah, Suci Siti; A, Triasianingrum (Jurnal Visi Ilmu Pendidikan, 2024)
This research is a qualitative reseach with descriptive analytic method. The purpose of this study was to describe an analyze science learning at Cikeas-Bogor School Of   Nature Midlle School. This research was carried out from January 2019 to Juny 2019 with several informants namely Science Teacher, Principal, Head Of Education Division, Head Of Research and Development, Head Of General Division, Vice Chancellor For Curriculum, Vice Chancellor For Student Affairs and Learners. This research was conducted with direct contact with the subject of research foun in the field and obtained two types of data, namely primary data derived   from interviews and observations, as well as secondary data derived from study documentation, based on data analysis, science learning based nature is divided into 3 processes, namely planning, implementation and evaluation. Learning planning uses thematic integrative. This competency refers to 5 basic concepts of   Nature Cikeas School of nature, namely morality, leadership, scientific logic, entrepreneurship and nationality. Continued by making spider web and outlining it into learning activities with scientific approaches. Learning method with nature, as well as learning resources through book and internet. The implementation of learning consists of school learning, RLE (Relife Education) and PBL (Project Based Learning) carried out in a relaxed and fun way, done in nature, and parents of students play an active role in the implementation of learning. Learning evaluation consists of the   percentage of results of RLE (Relife Education), test in the form of descriptions, PBL (Project Based Learning) and RPD (Raport Self Potential). Learning with nature is a learning method that is applied in science learning to teach students to build logical thinking.     Keywords: Science   Learning Based Nature, Learning Planning , Implementation Learning, Evaluation Learning, Learning With Nature.      AbstrakPenelitian ini merupakan penelitian kualitatif dengan metode deskriptif analitik. Tujuan dilakukannya penelitian ini untuk mendeskripsikan dan menganalisis pembelajaran sains berbasis alam di SMP Sekolah Alam Cikeas-Bogor. Penelitian ini dilaksanakan mulai dari Januari 2019 sampai Juni 2019 dengan beberapa informan yaitu Guru Sains, Kepala Sekolah, kepalaa. Divisi Pendidikan, kepala Divisi Litbang, kepala. Divisi Umum, Wakil kepala sekolah Kurikulum, Wakil kepala sekolah Kesiswaan dan Peserta Didik. Penelitian ini dilakukan dengan kontak langsung terhadap subjek penelitian yang terdapat di lapangan dan diperoleh dua jenis data yaitu data primer berasal dari wawancara dan observasi, serta data sekunder yang berasal dari studi dokumentasi. Berdasarkan analisis data, pembelajaran sains berbasis alam terbagi menjadi 3 proses yaitu perencanaan, pelaksanaan dan evaluasi. Perencanaan pembelajaran menggunakan tematik integratif. Kompetensi ini mengacu pada 5 konsep dasar Sekolah Alam Cikeas yaitu akhlakul karimah, kepemimpinan, logika ilmiah, kewirausahaan dan kebangsaan. Dilanjut dengan membuat Spider Web dan menguraikannya menjadi aktivitas pembelajaran dengan pendekatan scientifik. Metode belajar bersama alam, serta sumber belajar melalui buku dan internet. Pelaksanaan pembelajaran terdiri dari pembelajaran disekolah, RLE (Relive Education) dan PBL (Project Based Learning) dilaksanakan secara santai dan menyenangkan, dilakukan di alam, dan orang tua peserta didik berperan aktif dalam pelaksanaan pembelajaran. Evaluasi pembelajaran terdiri dari persentasi hasil RLE (Relive Education), tes dalam bentuk uraian, PBL (Project Based Learning) dan RPD (Rapot Potensi Diri). Belajar bersama alam merupakan metode pembelajaran yang diaplikasikan dalam pembelajaran sains untuk membelajarkan peserta didik membangun logika berpikir.Kata Kunci: Pembelajaran Sains Berbasis Alam, Perencanaan Pembelajaran, Pelaksanaan Pembelajaran, Evaluasi Pembelajaran, Belajar Bersama Alam.